The Impact of Credit on Productivity and Growth of Rural Nonfarm Enterprises - Maria Lucila A. Lapar (Philippine Institute for Development Studies (PIDS), 1994)
This study looks at the status of rural nonfarm enterprises (RNEs) in the Visayas area. Descriptive statistics indicate that majority of the RNEs are micro- and cottage-sized enterprises managed by the owner/operator only. Very few can be considered small-scale. Major activities undertaken are manufacturing, trading and services accounting for 31, 41 and 28 percent of the total RNEs surveyed.
Keywords: 330; productivity; rural sector; rural nonfarm enterprise; fiscal policy; farm lands